ANALISIS PENGETAHUAN DAN SIKAP KESEHATAN REPRODUKSI SISWA SMP NEGERI 3 MALUNDA - Lamua, Hasrawati (Universitas Cokroaminoto Palopo, 2025)
This research is a quantitative research using a survey method which aims to determine the level of knowledge and attitudes about reproductive health of students at SMP Negeri 3 Malunda. The population in this study was Class IX of SMP Negeri 3 Malunda, sampling used the census method to obtain a sample size of 91 students. The research instrument used was questions about reproductive health, a total of 25 items and 25 questionnaire statements about attitudes. The research data was analyzed by calculating the average and percentage and then categorizing it. The research results show that the level of knowledge of Class IX students at SMP Negeri 3 Malunda is included in the interval category 71 to 86 with the description